Communication Process And Evaluation In The Implementation Of Modern Retail Policy In Dki Jakarta - Budi Santoso; Sunarto Sunarto; Bernard Hasibuan; Dewi Widowati (Green Publisher Indonesia, 2021)
Communication in the effective implementation of modern retail policies in DKI Jakarta will reduce the problems that arise in the modern retail sector. Modern and traditional retail will actually need and complement each other. The purpose of this study is to determine the ongoing communication process and evaluation of communication, so that problems will not arise and repeat themselves. This study uses systems theory from Katherine Miller, where there are three system concepts, namely system components, system processes and system properties. The three system concepts are to find out how the process and evaluation of communication work. This study uses a qualitative descriptive approach with a case study methodology. The communication process, both internal and external, is more of a procedure, so it is not yet fully an evaluation tool. Various communication evaluation efforts are more likely to be carried out to facilitate communication. The feedback process has not been responded well, so the resolution is still temporary. Based on the results of this study, the process and evaluation of communication in the implementation of modern retail needs to be prioritized on good message management. Feedback needs to be studied more deeply, especially in external communication. Feedback from retailers can be used as an evaluation of why the implementation is running as expected.